A robust nonlinear stabilizer as a controller for improving transient stability in micro-grids. (January 2017) - Azimi, Seyed Mohammad; Afsharnia, Saeed
Abstract: This paper proposes a parametric-Lyapunov approach to the design of a stabilizer aimed at improving the transient stability of micro-grids (MGs). This strategy is applied to electronically-interfaced distributed resources (EI-DRs) operating with a unified control configuration applicable to all operational modes (i.e. grid-connected mode, islanded mode, and mode transitions). The proposed approach employs a simple structure compared with other nonlinear controllers, allowing ready implementation of the stabilizer. A new parametric-Lyapunov function is proposed rendering the proposed stabilizer more effective in damping system transition transients. The robustness of the proposed stabilizer is also verified based on both time-domain simulations and mathematical proofs, and an ultimate bound has been derived for the frequency transition transients. The proposed stabilizer operates by deploying solely local information and there are no needs for communication links. The deteriorating effects of the primary resource delays on the transient stability are also treated analytically. Finally, the effectiveness of the proposed stabilizer is evaluated through time-domain simulations and compared with the recently-developed stabilizers performed on a multi-resource MG. Highlights: The exponential suppression of the large transition transients during mode transitions. The robustness of the proposed stabilizer during mode transitions is evaluated. Ultimate bounds for the power angle and frequency deviations have been derived. Using solely local information to damp the power angle, frequency and voltage transients. Influences of the primary resource delays in the transition transients are evaluated.